Facile synthesis of poly(3, 4-ethylenedioxythiophene) and poly(bis-3, 4-ethylenedioxythiophene) via UV-irradiation polymerization and their reduction/iodine oxidation post-treatment for the application as counter electrodes for dye-sensitized solar cells. (1st August 2019) - Zhang, Rui; Xu, Ji; Qian, Junning; Xia, Jiangbin
Abstract: Conductive poly(3, 4-ethylenedioxythiophene) and poly(bis-3, 4-ethylenedioxythiophene) had been firstly synthesized by UV-irradiation of monomers of 5, 7-diiodo-2, 3-dihydro-thieno[3, 4-b][1, 4]dioxine and 7, 7′-diiodo-2, 3, 2′, 3′-tetrahydro-[5, 5']bi[thieno[3, 4-b][1, 4]dioxinyl]. To prepare conductive polymer counter electrodes for dye-sensitized solar cell, their UV polymerization (UVP) optimization processes had been carefully carried out. In order to further improve photo-to-electric conversion efficiency, these UVP-polymer electrodes were treated through reduction-reoxidation (N2 H4 /I2 ) process. Our results showed that with and without post-treatment, poly(3, 4-ethylenedioxythiophene) counter electrode demonstrated DSC conversion efficiencies of 7.08% and 6.64% respectively, while the Pt electrode showed 7.78%. Our study indicated that UVP is an alternative facile method to prepare poly(3, 4-ethylenedioxythiophene) and poly(bis-3, 4-ethylenedioxythiophene) films and the iodine post-treated UVP-poly(3, 4-ethylenedioxythiophene) counter electrode showed comparable performance to those obtained through traditional chemical oxidation or electrochemical polymerization methods. Graphical abstract: Poly(3, 4-ethylenedioxythiophene) (PEDOT) and poly(bis-3, 4-ethylenedioxythiophene) (P(bis-EDOT)) have been firstly synthesized by UV-irradiation polymeriztion (UVP). These polymer films are post-treated through reduction-I2 reoxidation and further employed as counter electrodes in dye-sensitized solar cells. The results indicate that UVP is an alternative facile method to prepare PEDOT or P(bis-EDOT) counter electrodes and UVP-PEDOT demonstrates good photo-electron conversion efficiency of 6.4–7.1%.Image 1 Highlights: Poly(3, 4-ethylenedioxythiophene) (PEDOT) and poly(bis-3, 4-ethylenedioxythiophene) (P(bis-EDOT)) have been synthesized by UV-irradiation polymerization. Before and after iodine reoxidation, PEDOT and P(bis-EDOT) counter electrodes show conversion efficiencies of 6.3–7.1% for dye-sensitized solar cell.